2014
DOI: 10.1590/1678-41625707
|View full text |Cite
|
Sign up to set email alerts
|

A new surgical technique to treat corneal perforations using amniotic membrane and surgical adhesive

Abstract: The objectives of this study were to compare surgical techniques and the effects of using n-butyl 2-cyanoacrylate and bovine amniotic membrane to repair perforated lesions in corneas. Penetrating keratoplasty was performed in sixty New Zealand White rabbits under general anesthesia. Group 1 (G1) was treated with n-butyl 2-cyanoacrylate, group 2 (G2) received a fragment of amniotic membrane through the anterior chamber and application of n-butyl 2-cyanoacrylate over the lesion, group 3 (G3) was treated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…3C and 3F). This differs from the results of Pontes et al (2014), who described equivalence between the two types of collagen and organization of fibers at 30 days in all groups evaluated. Thus, it is suggested that the presence of BC/PCL and BC membranes slowed corneal stroma healing process.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…3C and 3F). This differs from the results of Pontes et al (2014), who described equivalence between the two types of collagen and organization of fibers at 30 days in all groups evaluated. Thus, it is suggested that the presence of BC/PCL and BC membranes slowed corneal stroma healing process.…”
Section: Resultscontrasting
confidence: 99%
“…At 21 days, there was a higher proportion of immature collagen fibers and disorganization of collagen fibers in all groups (Figs. 3B and 3E), agreeing with the results of Pontes et al (2014) that reported prevalence of immature collagen at 21 days after application of amniotic membrane and n-butyl-2-cyanoacrylate to treat penetrating injuries in rabbits' corneas. In the cornea, type I collagen is predominant, since type III is found in small quantities (Qazi et al 2010).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Because our group frequently uses the amniotic membrane in research and in the hospital routine (Pontes et al, 2011;Pontes et al, 2014), it was important to evaluate this medium aiming at creating a bank of this tissue to be used in the long term.…”
Section: Resultsmentioning
confidence: 99%
“…The amnion was manually separated from the chorion ( Figure 1A) (Kim & Tseng, 1995), mounted, epithelial face upwards, onto nitrocellulose paper ( Figure 1B), and cut into the size of 1.0 cm 2 . Subsequently, the fragment was placed in a sterile glass vial and covered with sterile glycerin 99% ( Figure 1C) (Pontes et al, 2014).…”
Section: Methodsmentioning
confidence: 99%